Managing the product development process. Part II: case studies. (1st January 1997) - Jenkins, S.; Forbes, S.; Durrani, T.S.; Banerjee, S.K.
In part I, the management of product development was studied, and a number of methodologies were assessed. The work identified the principle strengths and weaknesses contained within structured product development processes in use in industry today. These methodologies have been credited with a fair degree of success in improving the productivity and quality of the product development process. The aim of this paper is to describe how these methodologies are applied in a number of case study organisations, and to present proposals for the improvement and continued development of the product development management process. A proposed framework for product development is presented that may act as a guide for companies seeking to advance the quality of their current product development process.